Faktor-Faktor yang Mempengaruhi Kehamilan pada Remaja Putri Usia Tingkat SMA di Wilayah Kabupaten Sleman Tahun 2021 - Dini Melani; Sri Puji Ganefati; Any Ashari (Journal of Health (JoH), 2022)
The high rate of teenage pregnancy in the Special Region of Yogyakarta in 2021 is 406 cases and in Sleman Regency as many as 103 cases which are assumed to be the effect of the suboptimal PKPR stakeholders in carrying out their duties and functions. The method used in this research is mixed methods, combining quantitative and qualitative research. The research design used in this research is sequential explonatory. The population in this study, namely all teenage girls (15-19 years) who experienced pregnancy recorded in the working area of Sleman Regency in 2021 as many as 103 teenage girls. Knowledge about sex affects teenage pregnancy, while economic, socio-cultural, educational factors, parental influence, marital status, knowledge about reproductive health, access to information, knowledge about sex, PKPR, free sex with drugs, and contraceptive use do not affect teenage pregnancy. Optimizing stakeholder performance is carried out by listening to the needs of youth and strengthening the focus of the PKPR Public Health Center service target outside the building as well as providing youth services as needed. The PKPR primary stakeholder strategy is based on an analysis of the determinants of teenage pregnancy in the Sleman Regency Work Area by considering internal and external factors by overcoming the problem of knowledge factors that affect KTD in high school girls in the Kab. Sleman so that it complies with the 3 SN PKPR standards. Keywords: Pregnancy, Unwanted Pregnancy, Teenage Girls